Influence of Discounts and Bundling Strategies on Kahf Product Purchases in Bandar Lampung - M. Gifary Dharmayandaru; Aida Sari (Management Dynamics: International Journal of Management and Digital Sciences, 2025)
In an era marked by intensifying business competition, marketing strategies such as price discounts and bundling packages play a crucial role in shaping consumer purchasing behavior. These approaches are commonly employed to capture consumer interest and boost sales performance. This study aims to ex-amine the influence of price discounts and bundling strategies on consumer purchasing decisions re-garding Kahf products in Bandar Lampung. The research utilizes both primary data, collected through questionnaires administered to respondents, and secondary data. The sample consists of 130 respond-ents selected using a non-probability sampling approach with a purposive sampling technique. Analyti-cal methods applied include validity and reliability tests, multiple linear regression analysis, and hypothe-sis testing through t-tests, F-tests, and the coefficient of determination (R²). The findings reveal that both price discounts and bundling packages exert a positive and statistically significant effect on con-sumer purchasing decisions for Kahf products in Bandar Lampung. These results underscore the im-portance of effective promotional strategies, such as compelling price reductions and value-enhancing bundling offers, in stimulating consumer purchases and enhancing product competitiveness in the mar-ket.